Workplace Diversity and Organizational Effectiveness: Empirical Insight from Telecom Enterprise - Majekodunmi, Samuel Ayodele; Olayiwola, Peter O. (Jurnal Pendidikan Ekonomi, 2025)
This study fills gap in literature, and make empirical contributions. Dimensions of methodology engaged include survey research design, population (400 employees of a telecom company called Mobile Telephone Network. situated in Lagos State); Taro Yamane’s formular (sample 200); questionnaire; simple random sampling; data analyses (SPSS). Results indicate weak positive, but, significant relationship between gender diversity and organizational effectiveness. Outcomes also show strong positive, and significant relationship between cultural diversity and organizational effectiveness. Moreover, results reveal moderate positive, and significant relationship between age diversity and organizational effectiveness. In line with findings, this study concludes that there is statistically significant relationship between workplace diversity and organizational effectiveness in Mobile Telephone Network situated in Lagos State, and Nigeria is its host country. Sequel to findings, the study recommends that the company should consider career development programs to support underrepresented gender, and implement flexible work policies to engage diverse gender. Keywords: workforce, organizational, empirical, telecom